Footboard and seat kinetic changes associated with stroke rate on a kayak ergometer - Bugeya Miller, K.; Goreham, J. A.; Frayne, R. J.; Ladouceur, M. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to determine if stroke rate effects anteroposterior, lateral, and vertical forces on the kayak`s footboard and seat. Participants (n=10), with a year or more of competitive kayaking experience, completed four 30-second trials on a kayak ergometer at different stroke rates (60 strokes per minute (spm), 80 spm, 100 spm, and maximum spm). Mean force, impulse, and impulse*stroke rate were identified for the footboards, and seat, separately within each trial (ten single strokes). Interestingly, both anteroposterior and lateral axes kinetic adaptations to stroke rate occurred on the left footboard whereas the right footboard presented only lateral adaptations.